Unsaturated fatty acids in antarctic bacteria - Garba, Lawal; Latip, Wahhida; Mohamad Ali, Mohd Shukuri; Oslan, Siti Nurbaya; Raja Abdul Rahman, Raja Noor Zaliha (Academic Journals, 2016)
Unsaturated Fatty Acids (UFAs) play a vital role in membrane lipids fluidity which maintains its structural integrity and also, are nutritionally and pharmaceutically important. Fish and vegetable oils are the major sources of the so-called essential fatty acids required for normal physiological activities of the body. However, the increasing demands for these fatty acids require more reliable, flexible and cheaper alternative sources. Antarctic bacteria can produce large amounts of unsaturated fatty acids which can be enhanced using simple biotechnological tools. To achieve this, five isolates of Antarctic bacteria were grown at low temperature and analysed for cellular fatty acids using Gas Chromatography Mass Spectrometry (GCMS). The results obtained revealed high amount of unsaturated fatty acids in virtually all the bacteria. Highest amount was recorded in Arthrobacter sp., 3B (47.24%) followed by Pseudomonas sp., A8 (45.09%), Pseudomonas sp., A3 (33.17%) and Arthrobacter sp., PB (31.92%). The results obtained suggest that the bacteria could be used to enhance essential fatty acids production through metabolic engineering for industrial applications.